Optical properties of polydisperse submicrometer aggregates of sulfur-containing zinc oxide consisting of spherical nanocrystallites - Bosshard, Gabriela Z.; de Souza e Silva, Juliana Martins; Lima, Sergio A. M. [UNESP]; Mazali, Italo O.; Sigoli, Fernando A. (Royal Soc Chemistry, 2011)
Spherical microparticles formed by agglomerated spherical nanocrystals of sulfur-containing ZnO were prepared by homogeneous precipitation of ZnS followed by thermal treatment under an air atmosphere. The samples were characterized by thermogravimetry (TG), X-ray diffraction (XRD) and Raman, UV-Vis diffuse reflectance (DRS) and photoluminescence (PL) spectroscopies. The particle morphologies were observed by transmission and scanning electron microscopies (TEM and SEM), showing that spherical microparticles of sulfur-containing ZnO are formed by aggregates of 25 nm spherical nanocrystallites. XRD and TEM results show the presence of ZnO and ZnS phases for short time thermal treatments and only the ZnO wurtzite phase for longer thermal treatments. The presence of Zn-S bonds in sulfur-containing zinc oxide decreases the ZnO band gap energy as verified by DRS, probably due to a valence band offset.